Influencing mechanisms of live streaming influencer characteristics on purchase intention: The mediating role of emotional trust - Rong Zhou; Angathevar Baskaran (PLoS ONE, 2025)
Live streaming e-commerce emphasizes the role of live streaming influencers and the dynamic interactions between viewers and live streaming influencers. Utilizing data collected from 400 questionnaires, this study delves into the mechanisms through which characteristics of live streaming influencers influence consumer purchase intentions, with a focus on consumer emotional trust as a mediating variable as well as consumer education level, age, perceived risk, and live-stream engagement as moderating factors. The findings indicate that the traits of live streaming influencers have a positive effect on consumers’ intent to purchase. Emotional trust mediates the influence of live streaming influencer characteristics on purchase intention. Consumers’ educational level positively moderates the relationship between the professionalism and homogeneity of influencers and their purchase intentions, while it negatively moderates the relationship between influencers’ attraction and interactivity with purchase intentions. Additionally, the age of consumers positively moderates the link between the professionalism of influencers and purchase intentions, but negatively moderates the links between homogeneity, attraction, and interactivity of influencers and purchase intentions. Furthermore, both consumers’ educational level and age positively moderate the impact of emotional trust on purchase intentions. Lastly, perceived risk and live-stream engagement respectively exert negative and positive moderating effects on the influence of influencer professionalism and attraction on purchase intentions. The study contributes to influencer marketing theory by adopting an innovative approach to systematically investigate the collective influence of all four live streaming influencer characteristics (professionalism, homogeneity, attraction, and interactivity) within a comprehensive framework.